A simple LC–MS/MS method for the determination of cortisol, cortisone and tetrahydro-metabolites in human urine: Assay development, validation and application in depression patients - Zhai, Xuejia; Chen, Fen; Zhu, Chaoran; Lu, Yongning (Journal of pharmaceutical and biomedical analysis, 2015)
•A LC–MS/MS method for simultaneous determination of F, E THF, 5α-THF and THE in human urine has been developed and validated.•The nocturnal urine concentrations of F, E THF, 5α-THF and THE in healthy adults and depression patients were analyzed.•The procedure of sample preparation was simple.•The real human urine was used in the method validation. Chronic stress as well as major depressive disorders is associated with cortisol metabolism. Two enzymes modulate cortisol (F) and cortisone (E) interconversion: 11β-hydroxysteroid dehydrogenase type 1 and type 2 (11β-HSD1 and 11β-HSD2). Furthermore, F and E were inactivated by 5α and 5β reductases to their tetrahydro-metabolites: tetrahydrocortisol (THF), allo-tetrahydrocortisol (5α-THF) and tetrahydrocortisone (THE). To better understand depression a LC-MS/MS method for simultaneous determination of F, E THF, 5α-THF and THE in human urine has been developed and validated. The quantification range was 0.1–160ngmL−1 for F and E, and 0.2–160ngmL−1 for the tetrahydro-metabolites, with >86.1% recovery for all analytes. The nocturnal urine concentrations of F, E and tetrahydro-metabolites in 12 apparently healthy male adult volunteers and 12 drug-free male patients (age range, 20–50 years) with a diagnosis of depression were analyzed. A series of significant changes in glucocorticoid metabolism can be detected: F/E ratios and (THF+5α-THF)/THE ratios as well as F and THF concentrations were significantly higher in depression patients than in healthy subjects (p<0.05); 5α-THF/F ratios, 5α-THF/THF ratios as well as 5α-THF concentrations were significantly lower in depression patients (p<0.05). The results pointed to the decreased 11β-HSD2 activity and a dysfunction in the 5α-reductase pathway in depressed patients. This method allows the assessment of 11β-HSD1/2 and 5α/β-reductase activities in a single analytical run providing an innovative tool to explain the potential etiology of depression.